2016
DOI: 10.1186/s12885-016-2974-x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective paired study: efficacy and toxicity of nimotuzumab versus cisplatin concurrent with radiotherapy in nasopharyngeal carcinoma

Abstract: BackgroundTo compare efficacy and toxicity of nimotuzumab versus cisplatin (CDDP) concurrent with intensity modulated radiation therapy (IMRT) in patients with nasopharyngeal carcinoma (NPC).MethodsWe retrospectively reviewed patients with NPC from September 2008 to November 2013. The synchronous regimens included h-R3/RT (nimotuzumab and radiotherapy) one time per week for 6–8 weeks and CDDP/RT (cisplatin and radiotherapy) every three weeks for 2–3 cycles. All patients in our analysis completed the planned IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
0
18
1
1
Order By: Relevance
“…To date, there are only four studies of small sample size about addition of h-R3 to RT or CCRT for NPC patients. In a retrospective paired study by Li et al [31] , the OS and PFS rates for h-R3/RT treatment group were lower than those for cisplatin/RT treatment group, but in stage II or older than 60 years subgroup, there were no significant differences for the OS and PFS. Zhai et al reported that addition of h-R3 to IMRT showed promising locoregional control and survival outcomes for LA NPC patients [32] .…”
Section: Discussionmentioning
confidence: 89%
“…To date, there are only four studies of small sample size about addition of h-R3 to RT or CCRT for NPC patients. In a retrospective paired study by Li et al [31] , the OS and PFS rates for h-R3/RT treatment group were lower than those for cisplatin/RT treatment group, but in stage II or older than 60 years subgroup, there were no significant differences for the OS and PFS. Zhai et al reported that addition of h-R3 to IMRT showed promising locoregional control and survival outcomes for LA NPC patients [32] .…”
Section: Discussionmentioning
confidence: 89%
“…In the retrospective paired study by Li et al 36 , the OS and PFS rates for the nimotuzumab/RT treatment group were lower than those for cisplatin/RT treatment group, but in the stage II or the older than 60 years subgroups, no significant differences were seen for OS and PFS. Zhai et al 29 reported that the addition of nimotuzumab to IMRT showed promising locoregional control and survival outcomes for LA NPC patients.…”
Section: Discussionmentioning
confidence: 90%
“…To date, only four small-scale studies on adding nimotuzumab to RT or CCRT for NPC patients have been conducted. In a retrospective paired study by Li et al [ 33 ], the OS and PFS rates for the nimotuzumab/RT treatment group were lower than those for cisplatin/RT treatment group, but in the stage II or the older than 60 years subgroups, no significant differences were seen for OS and PFS. Zhai et al reported that the addition of nimotuzumab to IMRT showed promising locoregional control and survival outcomes for LA NPC patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%